The Effect of Direct Compensation and Work Motivation on Employee Performance: Study at A Government Office in Bandung Regency - Awal Purnomosidi; M. Sidik Priadana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2020)
This study aimed to determine the effect of direct compensation and work motivation on employee performance—this study conduct by taking a sample of employees at one of the government offices in Bandung Regency. The research method used is a qualitative method with a total of 50 respondents using path analysis techniques. As for his research results, there is a significant effect of direct compensation and work motivation on employee performance either partially or simultaneously. Direct compensation and work motivation together affect employee performance by 64.04%. The proportionate amount of influence caused by other variables other than direct compensation and work motivation is 35.98%. The study results recommend that direct compensation and efforts to increase work motivation should always increase performance according to what has been determined.